The use of an iPad to collect patient-reported functional outcome measures in hand surgery - Yaffe, Mark (Hand (N Y), 2015)
BACKGROUND: The purpose of this study was to evaluate (1) patient preferences regarding iPad and paper-based questionnaires, (2) the efficacy of iPad and paper questionnaires in a hand surgery practice, (3) the influence of questionnaire length on patient preferences and data collection, and (4) patient characteristics associated with a preference for iPad-based questionnaires. METHODS: Two hundred total patients in a single hand surgery practice were randomly assigned to one of four groups. Each group completed either the Michigan Hand Questionnaire (MHQ) or QuickDASH (QD) using either an iPad or pen and paper. Patient preferences, questionnaire completion and timing, and demographic data were analyzed. RESULTS: The use of an iPad was associated with a statistically stronger preference for the same delivery format in the future compared to paper for the MHQ (93.9 vs 52.1 %, p < 0.001) and QD (90.0 vs 41.7 %, p < 0.001). The MHQ iPad group found the survey “physically easy” more often compared to the MHQ paper group, while no difference was found among QD groups. Questionnaire timing between iPad and paper groups was similar for the MHQ but statistically longer with the iPad for QD. A significantly higher proportion of patients who preferred the iPad were under the age of 50 compared to those who preferred paper. CONCLUSIONS: The addition of an iPad is an efficient and preferable questionnaire format for functional outcome assessment in a hand and upper extremity surgery practice setting. The iPad is particularly preferable for longer outcome questionnaires and for patients under the age of 50.